(untitled) (EAAE Annual Conference Proceedings, 2023)
People must be aware of architecture and related sciences and technologies, and architectural education to nurture conscious citizens is as important as it is for professionals. A recent quantitative survey with 2,000 respondents in Japan revealed only about 15% are interested in ‘shelter’ out of three essentials in everyday life: food, clothing, and shelter. They did not acknowledge architecture as essential in their lives.